Amniotic membrane-derived stem cells: immunomodulatory properties and potential clinical application - Insausti CL (Dove Medical Press, 2014)
Carmen L Insausti,1 Miguel Blanquer,1 Ana M García-Hernández,1 Gregorio Castellanos,2 José M Moraleda11Unidad de Trasplante Hematopoyético y Terapia Celular, 2Servicio de Cirugía, Hospital Clínico Universitario Virgen de la Arrixaca, IMIB, Campus Mare Nostrum, Universidad de Murcia, El Palmar, Murcia, SpainAbstract: Epithelial and mesenchymal cells isolated from the amniotic membrane (AM) possess stem cell characteristics, differentiation potential toward lineages of different germ layers, and immunomodulatory properties. While their expansion and differentiation potential have been well studied and characterized, knowledge about their immunomodulatory properties and the mechanisms involved is still incomplete. These mechanisms have been evaluated on various target cells of the innate and the adaptive system and in animal models of different inflammatory diseases. Some results have evidenced that the immunomodulatory effect of AM-derived cells is dependent on cell-cell contact, but many of them have demonstrated that these properties are mediated through the secretion of suppressive molecules. In this review, we present an update on the described immunomodulatory properties of the derived amniotic cells and some of the proposed involved mechanisms. Furthermore, we describe some assays in animal models of different inflammatory diseases which reveal the potential use of these cells to treat such diseases.Keywords: epithelial cells, mesenchymal cells, cell therapy, immunomodulation